The Association of Mammography Environment and Image Quality. Issue 5 (17th July 2020) - Sarquis-Kolber, Shakira; Schilling, Kathy; Hanney, William J; Kolber, Morey J
Abstract: Objective: This study sought to determine if a mammogram performed in a multi-sensory environmental upgraded room (UR) is associated with improved image quality when compared to a standard room (SR). Methods: A retrospective analysis (interrupted time series design) of compression force and posterior nipple line (PNL) measurements was performed on 303 women (mean age 60.9 years) who underwent screening mammography for 2 consecutive years (year 1 in SR, year 2 in UR) at a single outpatient facility. Using the Picture Archiving Communication System (PACS), craniocaudal (CC) and mediolateral oblique (MLO) images for the two years were reviewed. The PNL was measured for the CC and MLO images bilaterally using the embedded tools in the PACS software. Posterior nipple line and compression force were analyzed using a paired t-test. Bland–Altman plots were used to obtain 95% limits of agreement (LOA) between the UR and SR. Results: Image quality as determined by PNL measurement distance was greater in the UR ( P < 0.001) when compared with the SR, with similar compression force ( P ≥ 0.14). Mean PNL measurement differences ranged from 5.0 to 6.2 mm greater in the UR, whereas mean compression force differences ranged from -2.4 to 1.5 newtons. The 95% LOA suggest that PNL measurement differences between the UR and SR can vary by -11.0 to 27.0 mm. Conclusion: Environmentally modifying mammography rooms may improve image quality with regard to PNL measurements without increasing compression force.